Analisis Interpretasi Pesan dan Pembentukan Sosiogram Pidato Perdana Gibran Rakabuming Cawapres 2024 Pada Channel Youtube KompasTV - Abadi, Medi Trilaksono Dwi; Sagita, Virginia Ayu; Fariszy, Revta; Ratna, Vegasari Adya (Jurnal Paradigma, 2024)
The Indonesian nation will be facing a political party, namely the election of the president and vice president (Pilpres) in February 2024. Prabowo Subianto's second-ranked presidential candidate has officially announced his vice president's candidate, Gibran Rakabuming. This research was conducted to identify the formation of meaning and sociograms in the video footage entitled [FULL]: Pidato Perdana Gibran Rakabuming di Deklarasi Capres-Cawapres pada akun Youtube KompasTV on the YouTube channel of KompasTV. The method used is Reception Network Analysis (RNA) which is a method of data analysis by combining the method of reception analysis (reception analysis) and method of social network analysis. (social network analysis). The results of the analysis showed that the number of comments on the video amounted to 10,749 comments and managed to collect 9,207 comments that attracted a audience of 1,783,026 views. The total degree in the Gibran video network is 7,807 nodes and 17,393 edges. An account with the name “@no-ub3dq” or has another name “block a” becomes the account that has the highest posting rating. Clusters are automatically identified using the FastGreedy algorithm. The process of data visualization using DrL with the results of sociogram analysis Who responds Who shows: Diameter: 5, density: 0.000147, reciprocity: 0.000000, centralization: 0.001523, and modularity (modularity): 0.993400. The results of the digestive analysis showed that netizens' perceptions of the messages from Gibran's speeches vary due to different contexts. The most digestive response to hegemonic dominant positions is because of netizens who serve as political buzzer. Negotiating positions detected were 4 netizens, and opposition positions were detected 4 who were also suspected political buzzers from the capres fort and other cawapres.